Is the Chinese Anticorruption Campaign Authentic? Evidence from Corporate Investigations - Griffin, John M.; Liu, Clark; Shu, Tao (Management Science, 2022)
This paper examines whether the massive Chinese anticorruption campaign ensnares corrupt firms, contains a political component, and reduces corporate corruption. Consistent with the campaign’s stated objectives, investigated executives are more likely to come from Chinese firms with characteristics commonly associated with measures of poor governance, self-dealing, and inefficiencies. However, affiliations with prominent investigated political leaders increase investigation likelihood, while university affiliations with current central leadership decrease investigation likelihood, possibly indicating political partiality. Except for reported entertainment expenditures and chief executive officer pay, there has been little evidence of a substantial overall decrease in measures of potential corporate corruption. This paper was accepted by Tomasz Piskorski, finance.